INVESTIGATION OF MECHANICAL CHARACTERISTICS OF LIGHTWEIGHT CONCRETE USING ENVIRONMENTALLY FRIENDLY LIGHTWEIGHT AGGREGATES - Lisa Oksri Nelfia; Nazifa Sekarningtyas; Agung Sumarno; Astri Rinanti; Ouali Amiri (Universitas Trisakti, 2024)
This study aims to investigate the mechanical properties of lightweight concrete using lightweight aggregate and analyze the impact of silica fume on enhancing its compressive strength. The main objective of this study was to improve the value of industrial waste by utilizing GGBFS as a substitute for cement. Four alternative compositions have been used to produce samples of lightweight concrete. The coarse aggregate is substituted with 100% lightweight expanded clay aggregate, whereas the fine aggregates are replaced with 100% vermiculite and 100% polystyrene bead waste. A combination of 20% GGBFS and 10% silica fume is employed for cement replacement. The materials used throughout this study consist of aluminum powder and superplasticizer. The workability, compressive strength, tensile strength, and specific gravity of concrete will be determined by testing. The waster curing will be carried out on cylindrical concrete specimens 200 mm in height and 100 mm in diameter. Experimental results showed that the concrete mixture consisting of 80% cement and 20% GGBFS as binders, along with lightweight expanded clay aggregate as coarse aggregate and vermiculite as the fine aggregate, exhibits the highest compressive strength compared to other lightweight concrete mixtures.